Pelestarian Aset Budaya Permainan Congkak Melalui Desain Karakter Untuk Anak - Vina Dwi Sartika; Sri Wulandari; Alfian Candra Ayuswantana (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2023)
Traditional games are now disappearing due to the existence of games from foreign nations which are circulating in the form of online games. Games that can divert children's attention and interest in traditional Indonesian games. Through games, children are able to feel various feelings of joy or sadness, playing also involves interactions with each other or opponents. To achieve that feeling can be found by playing traditional games. This atmosphere can be found in traditional games. Based on this, the writer is interested in designing a character design about a traditional Indonesian game, namely the game Congklak. This design uses qualitative research methods with data collection techniques in the form of interviews, observation and literature studies. The results of this design are in the form of 2D-based animated characters which will later be implemented in various communication media. The design of this character design is a way to preserve Indonesian original cultural assets and educate the public about traditional games so that their existence is maintained.